2019
DOI: 10.1002/masy.201900036
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinylpyrrolidone (PVP) with Ammonium Iodide (NH4I) and 1‐Hexyl‐3‐Methylimidazolium Iodide Ionic Liquid Doped Solid Polymer Electrolyte for Efficient Supercapacitors

Abstract: Ionic liquid-doped poly(vinylpyrrolidone), ammonium iodide (NH 4 I) ion conducting polymer electrolytes are prepared by solution cast technique. Ionic liquid (IL), 1-hexyl-3-methylimidazolium (HMImI) is then added to increase the ionic conductivity of polymer electrolytes by reducing the crystallinity of polymer electrolyte. Fourier transform infrared spectroscopy confirms the complex formation as well as composite nature. Polarized optical microscopy affirms the reduction of crystallinity in polymer electroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Interestingly, the maximum conductivity of the polymer electrolyte (PVP + 40 wt% NH 4 I + 30 wt% EC) shows highly dense amorphous morphology (more blackish nature) which affirms reduction in crystalline nature (more amorphous). As we know from the reported literature that amorphous morphology of a polymer film leads to the high ionic conductivity 23,2427 and hence POMs confirm our results obtained in XRD measurement.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, the maximum conductivity of the polymer electrolyte (PVP + 40 wt% NH 4 I + 30 wt% EC) shows highly dense amorphous morphology (more blackish nature) which affirms reduction in crystalline nature (more amorphous). As we know from the reported literature that amorphous morphology of a polymer film leads to the high ionic conductivity 23,2427 and hence POMs confirm our results obtained in XRD measurement.…”
Section: Resultssupporting
confidence: 91%
“…In Figure 5, the spectrum of PVP (black color) contains the peaks at 1737, 1640, 1495, 1424, 1443, 1462, 1294, 1320, 1294, and 844 which corresponds to C=O stretch, –C=C– stretch, C–C stretch, C–H bend, C–N stretch, and C–O stretch. The FTIR spectra of PVP + 40 wt% NH 4 I have been reported elsewhere by our group 27 with peak assignment. On adding 30 wt% EC on the host polymer (PVP + 40 wt% NH 4 I), no extra peak was observed which affirms the composite nature of the plasticized polymer electrolyte film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 The C-H bending vibrational band of PVP blends and C-N stretching vibration appears at wavenumber 1431 cm −1 and 1284 cm −1 respectively. 30,31 The absorption peak of C-C bond at 1170cm −1 that indicates the presence of PVP and it is shifted to 1151 cm −1 due blending of starch. 24,27 The C-O and C-H stretching vibrational bands range from 900-1080 cm −1 indicates the presence of anhydroglucose and it is shifted to 929 cm −1 , 1080 cm −1 in blends.…”
Section: Ftir Analysismentioning
confidence: 99%
“…Imidazolium-based ionic liquids have been widely used as electrolyte components for lithium-ion batteries, [18,19] DSSCs, [20,21] supercapacitors [22,23] and field effect transistors [24,25] due to their low viscosity, [26,27] high conductivity, [28,29] non-flammability [30] and ease of functionalization through the available 1,3-positions. Regarding the conductivity of the ILs, it has been reported that oxygen atoms on the side chains of cation provide relatively higher conductivity values compared to the ones with the same length of n-alkyl chains due to ion-ion and van der Waals interactions.…”
Section: Introductionmentioning
confidence: 99%